Skema Internalisasi Nilai Heterogenitas dalam Moderasi Beragama Berbasis Etnosains - I Wayan Suasta (Jayapangus Press, 2026)
Hinduism can be understood integrally as a system of humanistic values that is not confined to a single, segmented terminology, but rather manifested through a set of universal values with broad relevance to social life. Values such as Satyam (truth), Dharma (virtue), Seva (service), Santih (peace), Prema (compassion), Manava Seva Mandawa Seva, Ahimsa Paramo Dharma, and Vasudaiva Kutumbakam represent ethical foundations that can be implemented across diverse social contexts. This study aims to analyze the contribution of Hindu religious education in fostering religious moderation and social acceptance of diversity through an ethnoscience-based perspective. The research employs a literature review method with a critical discourse approach to examine Hindu values that can be internalized within educational practices. The findings indicate that Hindu religious education plays a strategic role in cultivating awareness of diversity through the habituation of teachings such as Tri Kaya Parisudha, Satyam, Sivam, Sundaram, Seva, Ahimsa, and Prema as foundational principles leading to the realization of Santih (peace). In addition, local practices such as matilesang raga are understood as ethnoscience-based actions that strengthen the integration of religious values, culture, and local wisdom. This study concludes that the systematic internalization of Hindu values within ethnoscience-oriented education serves as a reconstructive strategy for promoting religious moderation, while simultaneously constructing harmony among religious values, culture, customs, and social norms within multicultural societies.